A Retospective Study on Causes of Lower Limb Amputation in Peshawar, Khyber Pukhtunkhwa - Kamran, Muhammad; Rasool, Arsalan; Ahsan, Zarafshan; Tahir, Muhammad; ur Rehman, Shafiq; Ahmed, Aqeel; Nauman, Muhammad (Pakistan Journal of Medical & Health Sciences, 2024)
Background: This study investigates the various causes of lower limb amputation in Peshawar, Khyber Pakhtunkhwa, highlighting the impact of environmental and societal factors on the prevalence of these amputations. Aim: To identify the major causes of lower limb amputation in Peshawar. Study Design: Retrospective study. Methods: A total of 100 questionnaires were completed by patients from different hospitals in Peshawar who met the inclusion criteria. Results: The leading cause of lower limb amputation identified in this study is bomb blasts, accounting for 45% of the cases. This high percentage is attributed to the prevalent terrorism in the region, with frequent bombings occurring in markets, schools, mosques, and army camps. The second leading cause is road traffic accidents (RTA), contributing to 20% of the amputations. The lack of adherence to traffic rules and regulations significantly contributes to this cause. Other identified causes include gunshots (18%), diseases (11%), trauma (3%), burns (2%), and congenital factors (1%). Conclusion: Bomb blasts are the predominant cause of lower limb amputation in Peshawar, making up 45% of the cases. Other causes such as RTA, gunshots, disease, trauma, and burns are also significant, with congenital causes being the least common at 1%.